Chaetonerius Hendel (Neriidae: Diptera) from the East African islands with description of four new species from Madagascar and the Comoros - Sepúlveda, Tatiana A.; Carvalho, Claudio J. B. De (Zootaxa, 2019)
Except for the introduced species, Telostylinus lineolatus Wiedemann, all Neriidae occurring in the Ethiopian Region belong to the genus Chaetonerius Hendel and only one species, C. alluaudi (Giglio-Tos), is known from the East African islands, described from Seychelles and also recorded for Madagascar and Mauritius. Herein, we describe four new species of Chaetonerius from the East African islands, including the first species of Neriidae from the Comoros (C. kotrbae sp. n.) and three new species from Madagascar (C. ebejeri sp. n., C. kirkspriggsi sp. n. and C. madagasikara sp. n.). Additionally, a redescription of C. alluaudi (Giglio-Tos) with new record for Réunion and a key for identification of Chaetonerius from the East African islands are provided.